ASPEK PSIKOLOGIS DAKWAH DALAM KISAH NABI NUH DI DALAM AL-QURAN - Zulhan Hasibuan, Muhammad; Nur Fadly, Muhammad (Al-I'jaz: Jurnal Kewahyuan Islam, 2021)
AbstractThis study explores the psychological lessons that can be learned from the mission of Prophet Noah as reflected in the Qur’an and its relevance for contemporary mission. Using a qualitative approach, this study analyzes Qur’anic texts related to Prophet Noah’s mission, focusing on the themes of steadfastness, emotional management, and communication strategies in the face of rejection. By integrating literature from the fields of psychology of religion, Islamic mission, and Qur’anic interpretation, this study highlights the psychological principles underlying Prophet Noah’s mission approach, such as mental resilience, patience, and empathy. The results show that these principles are not only essential in the context of mission in early Islam, but also provide valuable lessons for mission in the modern era, especially in overcoming the psychological and emotional barriers faced by contemporary audiences. This study emphasizes the importance of emotional intelligence, effective communication, and the ability to manage stress in enhancing the impact of mission in diverse and often resistant societies. This study contributes to the field of Islamic studies by bridging the gap between classical teachings and contemporary psychological insights, as well as providing practical recommendations for modern mission practice.Keywords: Preaching Leadership; Preaching Psychology; Prophet Noah; Psychological Resilience; Contemporary Preaching